Why “South”/“North” Framings are not Useful in a Shifting World Order - Hornidge, Anna-Katharina; Berger, Axel (CEBRI-Revista: Brazilian Journal of International Affairs, 2024)
An emerging multipolarity in which many transition economies employ "Global South" framings, often in contrast to a "Global North," defines international relations. This re-configuration of global discourses and power relations also occurs in the G20, which is led between 2022 and 2025 by countries from the "Global South." Against this backdrop, this article asks what this "Southernization" implies for the Think20, the think tank process accompanying the G20 by providing research-based policy advice and policy dialogue. In this text, we sketch out how the Think20 process during Brazil's G20 Presidency and beyond can be strengthened and further developed to bring together the different high-quality research insights represented in the network while forming epistemic friendships to support cooperative global governance.